THE EMPLOYEES’S ACTIVITIES IN WORKING ON ENGLISH DOCUMENTS AT PT. IRAMASUKA TOURS AND TRAVEL - Ansari Abdillah; M. Tahir; Amin, Fatimah Hidayahni (International Journal of Business English and Communication, 2023)
This research is descriptive qualitative research that aims to find out the activities of employers and employees in working on English documents at PT. Iramasuka. The subjects of this research were employers and employees. The sample consists of 4 respondents. In conducting this research, data were obtained using interview questions, observation checklist, and questionnaires. The results of the data shows that the activities carried out at PT. Iramasuka in the business communication division is correspondence conducted in the office, including making agreement letters, confirmation letters,reading and informing cooperation agreements. The product division creates and designs products to be marketed, discusses and provides suggestions and ideas for further products that have the potential to be marketed. In the promotion section, creative and attractive product ideas are designed so that they can attract the attention of customers. Based on the findings above, the researcher concluded that many activities through documents were carried out at PT. Iramasuka uses the English language and skills.